Low birth weight and the delay on the eruption of deciduous teething in children - Cristiane Ribeiro da Silva Castro; Maria Beatriz Barreto de Sousa Cabral; Eduardo Luiz Andrade Mota; Maria Cristina Teixeira Cangussu; Maria Isabel Pereira Vianna
Abstract Objectives: To analyze the association between low birth weight (LBW) and the occurrence of the delay on the eruption of deciduous teething (DEDT) in children from 04 to 30 months, living in Salvador, Bahia. Methods: A cross-sectional study involved 520 children at four to thirty months of age, from public, private and philanthropic daycares from two districts in Salvador. A descriptive analysis and unconditional logistic regression were done to estimate the odds ratios (ORs), using the Confidence Interval of 95% as a criterion for accepting associations. Poisson regression was used as an analytical strategy to obtain the prevalence ratio. Results: the prevalence of the delay on the eruption was 10.29%. There was a positive association between LBW and occurrence of DEDT among children with less than 24 months, both in the unadjusted model (PR=2.07, 95%CI= 0.96 4.44) as in the adjusted (adjusted PR=2, 27, 95%CI= 1.02 5.07). Conclusions: the variables of development and nutritional at birth and during the early life may be important predictors of the chronology of eruption. Further investigations should be carried out towards the adequate evaluation of the LBW role in the occurrence of the delay on the eruption.